Authorship policies of scientific journals. Issue 3 (29th December 2015) - Resnik, David B; Tyler, Ana M; Black, Jennifer R; Kissling, Grace
Abstract : We analysed the authorship policies of a random sample of 600 journals from the Journal Citation Reports database. 62.5% of the journals we sampled had an authorship policy. Having an authorship policy was positively associated with impact factor. Journals from the biomedical sciences and social sciences/humanities were more likely to have an authorship policy than journals from the physical sciences, engineering or mathematical sciences. Among journals with a policy, the most frequent type of policy was guidance on criteria for authorship (99.7%); followed by guidance on acknowledgments (97.3%); requiring that authors make substantial contributions to the research (94.7%); requiring that authors be accountable for the research as a whole (84.8%); guidance on changes in authorship (77.9%); requiring that authors give final approval to the manuscript (77.6%); requiring that authors draft or critically revise the manuscript (71.7%); providing guidance on corporate authorship (58.9%); prohibiting gift, guest or ghost authorship (31.7%); requiring authors to describe their contributions (5.3%); limiting the number of authors for some types of articles (4.0%) and requiring authors to be accountable for their part in the research (1.1%). None of the policies addressed equal contribution statements. Journals that do not have authorship policies should consider adopting or developing ones.